2011
DOI: 10.1007/s10508-011-9792-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-Erotic Cognitive Distractions During Sexual Activity in Sexual Minority and Heterosexual Young Adults

Abstract: The present study examined 100 lesbian and gay college students and 100 heterosexual students to determine whether group differences exist in frequency of a range of non-erotic cognitive distractions during sexual activity. Non-erotic cognitive distraction is a descriptive term for both self-evaluative cognitions related to physical performance and body image concerns, as well as additional cognitive distractions (e.g., contracting an STI or emotional concerns) during sexual activity. Participants were matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Even if the HIV-care has incredibly advanced, the "HIV shadow" still has a pervasive influence on gay men sexuality. MSM frequently report more distractive thoughts related to fear of STIs compared to heterosexual men [82]. In a group of Belgian HIV-positive MSM, 15% of men reported HSDD [83] and factors associated to lower desire were higher frequency of masturbation and having less sexual partners over time.…”
Section: Factors Influencing Gay Sexual Desirementioning
confidence: 94%
“…Even if the HIV-care has incredibly advanced, the "HIV shadow" still has a pervasive influence on gay men sexuality. MSM frequently report more distractive thoughts related to fear of STIs compared to heterosexual men [82]. In a group of Belgian HIV-positive MSM, 15% of men reported HSDD [83] and factors associated to lower desire were higher frequency of masturbation and having less sexual partners over time.…”
Section: Factors Influencing Gay Sexual Desirementioning
confidence: 94%
“…Although previous research suggests that SD and body image dissatisfaction are related (i.e., more body image concerns predict higher SD [6]), it is important to note that much of this work involves general questions about overall sexual satisfaction and does not particularize specific SD [21] [24]. Findings from our study suggest that, for gay men, certain types of SD (e.g., body embarrassment) may be more strongly associated with self-consciousness during physical intimacy than other types (e.g., erectile difficulties).…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach's alpha for the 17-item M-BISC was .92, which suggests good scale score reliability. Although the creation of the M-BISC has provided researchers with an opportunity to measure male body image concerns during sexual activity, the scale was validated with a predominately heterosexual sample (i.e., over 90% of the participants reported that they were "exclusively heterosexual" or "more heterosexual than homosexual") [ [21]. Furthermore, the few studies assessing body image and SD in men choose to isolate men's genital concerns in relation to sexual functioning (i.e., penis length and girth, circumcision status) [22][23] rather than explore the entirety of the male body.…”
Section: Male Body-image Self-consciousness Scale (M-bisc)mentioning
confidence: 99%
“…In addition, relative to women, men experience significantly more performance related concerns during sexual activity (Nelson & Purdon, 2011). Lacefield and Negy (2012) found that not only do gay men experience significantly more negative automatic thoughts during sex related to sexual performance, STI-related fears, and body image relative to heterosexual men, but they also experience more anxiety regarding these negative automatic thoughts during sex. These performance related fears included not being able to satisfy their partner and not being able to give their partner an orgasm, and are consistent with a strong underlying BSS.…”
Section: Belief In Sexual Stereotypesmentioning
confidence: 95%